2015
DOI: 10.1111/1467-8489.12098
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing farmers’ participation in contractual biodiversity conservation: a choice experiment with northern Australian pastoralists

Abstract: Private landholders’ contributions to biodiversity conservation are critical in landscapes with insufficient formal conservation reserves, as is the case in Australia's tropical savannas. This study reports results from a discrete choice experiment conducted with pastoralists and graziers across northern Australia. The experiment was designed to explore the willingness of pastoralists and graziers to sign up to voluntary biodiversity conservation contracts. Understanding preferences for contractual attributes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 45 publications
(45 reference statements)
2
64
1
Order By: Relevance
“…The negative sign was not expected and suggests a 'negative' bias toward the SQ, that is, a positive perception of changes. This is in contrast to other studies that have found positive bias toward SQ (Kenter et al 2011;Greiner 2015). One possible explanation for this negative bias for SQ is that, with the help of additional questions to clarify why respondents chose SQ, we have been able to screen out more protesters than other study.…”
Section: Parameter Estimatescontrasting
confidence: 94%
“…The negative sign was not expected and suggests a 'negative' bias toward the SQ, that is, a positive perception of changes. This is in contrast to other studies that have found positive bias toward SQ (Kenter et al 2011;Greiner 2015). One possible explanation for this negative bias for SQ is that, with the help of additional questions to clarify why respondents chose SQ, we have been able to screen out more protesters than other study.…”
Section: Parameter Estimatescontrasting
confidence: 94%
“…This was expected as the model did not include any business and social variables so as not to confuse the focus of this analysis on attitudinal and motivational influences. The influence of other factors is analysed elsewhere (Greiner, 2015).…”
Section: Choice Modelling Results: Influence Of Motivations and Attitmentioning
confidence: 99%
“…Respondents were asked to pick their preferred option ('1st preference') and subsequently indicate the least preferred then second preferred option in any given choice task. Table 3 provides an example of one discrete choice task with the 1st preference question only as the analysis shown here is restricted to the sub-set of 1st preference data, which has been shown to yield superior model results compared to the fully ranked data (Greiner, 2015).…”
Section: Choice Experimental Design and Analysismentioning
confidence: 99%
See 2 more Smart Citations